Discovery of a novel linc01125 isoform in serum exosomes as a promising biomarker for NSCLC diagnosis and survival assessment. (30th April 2021) - Xian, Jianfeng; Zeng, Yuyuan; Chen, Shizhen; Lu, Liming; Liu, Li; Chen, Jinbin; Rao, Boqi; Zhao, Zhuxiang; Liu, Jun; Xie, Chenli; Zhu, Lingling; Zhang, Duo; et al.
Abstract: A non-invasive method to distinguish potential lung cancer patients would improve lung cancer prevention. We employed the RNA-sequencing analysis to profile serum exosomal long non-coding RNAs (lncRNAs) from non-small cell lung cancer (NSCLC) patients and pneumonia controls, and then determined the diagnostic and prognostic value of a promising lncRNA in four datasets. We identified 90 dysregulated lncRNAs for NSCLC and found the most significant lncRNA was a novel isoform of linc01125. Serum exosomal linc01125 could distinguish NSCLC cases from disease-free and tuberculosis controls, with the area under the curve values as 0.662 [95% confidence interval (CI) = 0.614–0.711] and 0.624 (95% CI = 0.522–0.725), respectively. High expression of exosomal linc01125 was also correlated with an unfavorable overall survival of NSCLC (hazard ratio = 1.48, 95% CI = 1.05–2.08). Clinic treatment decreased serum exosomal linc01125 in NSCLC patients ( P = 0.036). Linc01125 functions to inhibit cancer growth and metastasis via acting as a competing endogenous RNA to up-regulate tumor necrosis factor alpha-induced protein 3 (TNFAIP3) expression by sponging miR-19b-3p. Notably, the oncogenic transformation of 16HBE led to decreased linc01125 in cells but increased linc01125 in cell-derived exosomes. The expression of linc01125 in total exosomes was highly correlated with that in tumor-associated exosomes in serum. Moreover, lung cancer cells were capable of releasing linc01125 into exosomes in vitro and in vivo . Our analyses suggest serum exosomal linc01125 as a promising biomarker for non-invasively diagnosing NSCLC and predicting the prognosis of NSCLC. Abstract : Our analyses suggest serum exosomal linc01125 as a promising biomarker for non-invasively diagnosing non-small cell lung cancer (NSCLC) and predicting the prognosis of NSCLC. Graphical Abstract: